The post-school education choices of young women in Australia and Canada - Austen, Siobhan; MacPhail, F. (CAER and IRRC, 2011)
Young Canadian women engage in post-school study at a much higher rate than their Australian peers, with a large part of the difference in this rate attributable to differences in rates of participation in the non-university sector. This article uses data from the Australian Longitudinal Surveys of Australian Youth and the Canadian Youth in Transition Survey to generate a unique cross-country comparison of the characteristics of young women engaged in different types of post-school education. The results highlight important differences in the role played by academic ability and parental resources in the allocation of educational ‘slots’ in the non-university sectors of the two countries. The results suggest that ‘second-tier’ post-school institutions could play a role in boosting rates of post-school education in Australia, with important consequences for the design of policy on this sector.